Evaluation of the Influence of Jiangxiang Reservoir Immersion on Corp and Residential Areas. (18th April 2018) - Chen, Jing; Huang, Yong; Yang, Yongmei; Wang, Jingjing
Abstract : Reservoir immersion is an environmental geological issue. Jiangxiang reservoir was taken as an example, where both analytical and numerical methods were employed to calculate the banked-up water level after reservoir impoundment, based on the hydrological, meteorological, geological, and hydrogeological conditions. The capillary rise height of soils in the reservoir area was determined through in situ measurement and laboratory analysis. The depth of foundation and crop roots in residential areas can be obtained by field investigation. The critical depth to groundwater was calculated according to the height of capillary rise and land elevation. Furthermore, the influence of reservoir immersion was evaluated, which provides a scientific basis for the relocation of people in reservoir areas, planting of crops, and project investment.